Strategi Manajemen Humas Dalam Memanfaatkan Teknologi Digital Di Kantor Kementrian Agama Kabupaten Lamongan - Archami, Virna Maulidiya; Kholis, Nur; Sulanam, Sulanam (JURNAL MANAJEMEN PENDIDIKAN, 2025)
PUBLIC RELATIONS MANAGEMENT STRATEGY IN UTILIZING DIGITAL TECHNOLOGY AT THE OFFICE OF THE MINISTRY OF RELIGION OF LAMONGAN REGENCYThe importance of the role of public relations in building a positive image of the institution through the use of digital technology, especially at the Office of the Ministry of Religious Affairs of Lamongan Regency. This study aims to examine public relations management strategies in facing challenges and optimizing communication with the public in the digital era at the Office of the Ministry of Religious Affairs of Lamongan Regency. The method used is qualitative with interview, observation, and documentation techniques. The results of the study indicate that the integration of digital technology in public relations activities can increase the efficiency of information dissemination, through the use of digital media such as Instagram, Facebook, TikTok, YouTube, and the official website. As well as strengthening the relationship between the institution and the public. However, at the Office of the Ministry of Religious Affairs of Lamongan Regency there are still obstacles in the form of cybersecurity and limited access in remote areas. From this study, it is necessary to strengthen the capacity of public relations human resources in the field of technology and the development of digital security policies to support the optimal achievement of institutional goals in the digital era.